Concentration and distribution of sialic acid in human milk and its correlation with dietary intake - Xie, Qiaoling; Xu, Yuhan; Zhang, Wei; Zhu, Meizhen; Wang, Xinyue; Huang, Jiale; Zhuang, Yingying; Lan, Hui; Chen, Xiaoxuan; Guo, Dongbei; Li, Hongwei (Frontiers in Nutrition, 2022)
Purpose: This study evaluates the content, distribution, and changing trend of sialic acid in human milk and the correlation between dietary intake of sialic acid and that in human milk. Methods: The study included 33 mothers of full-term and exclusively breastfed infants. At least 2 mL of milk was collected on the 3rd, 8th, 30th, and 90th day after delivery, and 24-hour diet recalls of the lactating mothers were obtained each time. The correlation of human milk sialic acid concentration with lactating women’s dietary sialic acid intake during lactation was analyzed by statistical analysis software SPSS. Results: The average concentration of sialic acid in colostrum, transition, and 1 and 3 months were 1,670.74±94.53 mg/L, 1,272.19±128.74 mg/L, 541.64±55.2 mg/L, and 297.65±20.78 mg/L, respectively. The total sialic acid concentration in colostrum was about 5.6 times higher than that at 3 months (P <0.001). The average dietary sialic acid intake of lactating mothers on the 2nd, 7th, 30th, and 90th day after delivery were 106.06±7.51 mg/d, 127.64±8.61 mg/d, 120.34±10.21 mg/d, and 95.40±6.34 mg/d respectively. The intake of sialic acid was relatively high on the 7th day, and there was no significant difference in dietary intake of sialic acid on different days (P <0.05). In addition, there was no correlation between the intake of dietary sialic acid and the content of total sialic acid and various forms of sialic acid in milk (P <0.05). Conclusion: Total sialic acid concentrations were highest in colostrum and decreased with lactation duration. Sialic acid in human milk is mostly oligosaccharide-bound, some protein-bound, and a little in the free form. The proportion of sialic acid in human milk is unchanged at different stages of lactation. In addition, the sialic acid in human milk is higher than dietary intake, without any correlation between them; the content in human milk mainly depends on the self-regulation of physiological needs.